Effect of Electro-acupuncture at Changqiang Acupoint on the Expression of BDNF Protein in Hippocampus CA3 of Rats with Autism - Xuejun ZHANG; Qianru HUANG; Lin Hong; Ping FU; Lingxiu RUAN (康复学报)
Objective:To explore the effects of electro-acupuncture at Changqiang acupoint on the BDNF protein expression in hippocampal CA3 region in rats with autism.Methods:Autism rat model was made by intraperitoneal injection of pregnant rats with valproate sodium (VPA).A total of 24 autism rats were divided into model group, Changqiang group and non-acupoint group, with 8 rats in each group;8 normal litter mate rat were used as blank group. The Changqiang group acupuncture Changqiang point 0.3 inch, using 0.5 inch homemade bipolar conjoined needle, electro-acupuncture 20 min,20 days a course of treatment; The non-acupoint group adopts the same method as the Changqiang group except the acupoints are different; The blank group and model group were kept under the same condition. Rats were weighed at different time points after birth (PN7,PN14,PN23 and PN34),using Morris water maze to evaluate learning and memory ability of rats, and using immunohistochemical to evaluate BDNF protein expression in hippocampal CA3 area of rats.Results:1. Weight: At PN34, weight of Changqiang group was higher than the model group (P<0.05); there was no statistical difference between non-acupoint group and model group (P>0.05).2. Morris sater maze: Compared with the blank group, average latency time of the model group was significantly prolonged, quadrant swimming time/total time of the original platform decreased significantly, with statistically significant difference (P<0.05); Compared with the model group, average latency time was significantly shortened, quadrant swimming time/total time of the platform increased significantly, with statistically significant difference (P<0.05), the average latency time of the non-acupoint group was significantly shortened, quadrant swimming time/total time of the platform increased significantly, with no statistically significant difference (P>0.05). 3. Immunohistochemistry: Compared with the blank group, the mean gray value of BDNF protein in model group increased significantly, with statistically significant differences (P<0.05); Compared with the model group, the mean gray value of BDNF protein in Changqiang group decreased, with statistically significant differences (P<0.05), the mean gray value of BDNF protein in non-acupoint group decreased, with no statistically significant difference (P>0.05).Conclusion:Electro-acupuncture at Changqiang acupoint can increase the expression of BDNF protein in the hippocampus CA3 region of autistic rats, and improving the growth, development and learning and memory abilities of autistic rats.